2000
DOI: 10.1177/088626000015011007
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Focused Cognitive Behavioral Therapy for Children and Adolescents

Abstract: This article reviews the four major components of trauma-focused cognitive behavioral therapy (CBT) for children and adolescents: exposure, cognitive processing and reframing, stress management, and parental treatment. For each component, background, description, and the current empirical support for including each of these components in the treatment of traumatized children is presented. Although there is growing empirical support for the efficacy of traumafocused CBT in decreasing psychological symptomatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
176
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(188 citation statements)
references
References 60 publications
5
176
1
2
Order By: Relevance
“…To explain this finding, it could be said that during TF-CBT sessions, the child's negative thoughts are dealt with and corrected and various techniques like thought stopping, thought-emotion relation finding, and daily thought recording are taught to decrease child's rumination (19). Thought stopping, as a method aiming to overcome cognitive distortion and worry, supports the child with thought processing because the method makes the child insightful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explain this finding, it could be said that during TF-CBT sessions, the child's negative thoughts are dealt with and corrected and various techniques like thought stopping, thought-emotion relation finding, and daily thought recording are taught to decrease child's rumination (19). Thought stopping, as a method aiming to overcome cognitive distortion and worry, supports the child with thought processing because the method makes the child insightful.…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness of medication-based therapies in minimizing abused children complications has been a matter of controversy and doubt in recent studies (19). In recent years, cognitive behavioral approach has been the dominant therapeutic approach in lessening the problems of abused victims.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrate a range of treatment modalities for addressing the enduring effects of child maltreatment and accompanying relevant comorbid conditions. Evidence suggests that trauma-focused cognitive-behavioral treatment shows special promise for some girls and young women [58][59][60][61]. This treatment approach, however, has not yet been studied in its application to crossover youth, and in fact, few studies have demonstrated the effectiveness of cognitive-behavioral treatment generally with adjudicated youth in a restricted setting, such as detention [62].…”
Section: Implications For Policy Programming and Practicementioning
confidence: 99%
“…These approaches can include psychoeducation, therapies designed to address trauma and its accompanying symptoms (e.g., cognitive therapies, desensitization therapies, prolonged exposure), emotional regulation and social skill-building, enhancing resiliency, and psychotropic medication management (Cohen, Mannarino, Berliner, & Deblinger, 2000;Jennings, 2008;NCTSN, 2007). This dualapproach to service delivery provides all those involved in client cases (e.g., case managers, clinicians, and administrators) with a common understanding and language surrounding the impact of trauma and its treatment.…”
Section: Trauma-informed Carementioning
confidence: 99%